Strategic Thinking Practices in Yemeni Small and Medium Sized Enterprises (SMEs) - Bahaj, Mohsen Hasan Ali (2010)
Strategic management scholars and practitioners concur that strategic thinking is one of the integral components of the strategic management, and consequently suggest that firms that infuse strategic thinking practices would be able to realize better performance through the formation and implementation of more innovative and effective strategies. Despite the proposition. the literature review indicated studies that examine strategic thinking remain limited. This research presents an attempt to explore the strategic thinking practices of small and medium size enterprise(SMEs) in Yemen. In this research, questionnaires were sent to 50 SMEs selected from the sampling frame. All of the 50 SMEs completed and returned the questionnaires providing a response rate of 100 percent. The findings of this study indicate that in general the SMEs adopt some form of strategic thinking practices. More specifically the SMEs that participated in this study tend to emphasize strategic thinking practices that include, obtaining foresight, holistic perspective, acquiring insight, focus on creativity pragmatic aspect maintaining objectivity achieving relative advantage and maintaining focus.